The Collateral Damage of C2C Communications on Social Networking Sites: The Moderating Role of Firm Responsiveness and Perceived Fairness. Issue 2 (2nd April 2016) - Adjei, Mavis T.; Nowlin, Edward L.; Ang, Tyson
Abstract : Social networking sites are important to firms as firms use them to communicate with their customers. This study investigates the overlooked collateral damage (the accidental negative outcomes that occur when customers communicate with each other via social networking sites) that customer-to-customer communications, through social networking, has for firms. Based on 3 experimental surveys with 614 participants, we found that information that is received publicly by way of social networking sites elicit higher levels of betrayal than information that is received via nonsocial networking platforms. Further, perceived betrayal increased negative word-of-mouth and patronage reduction. Fortunately, the study finds that perceived firm responsiveness and perceived fairness mitigate the negative impact of betrayal on both negative word-of-mouth and patronage reduction. Managerial and theoretical implications are provided.